Effect of silicon on protein and lignin contents of two annual flower species - Traspadini, Edilaine Istéfani Franklin; Mantovani, Cibele; Prado, Renato de Mello (Ornamental Horticulture, 2019)
The beneficial effect of silicon on plants is known, but there are no studies demonstrating the effect of this element on protein and lignin production in ornamental plants.This study aimed to assess the effects of monosilicic acid fertigation at 0, 2, 4, and 8 mmol L-1 of Si on protein and lignin production of two ornamental species: Viola x wittrockiana Gams ex Nauenb. & Buttler ‘Majestic Giants II Fire’ e Tagetes erecta L. ‘Hero’ (color mix). The experiment was installed in a 4 × 2 factorial arrangement using a completely randomized design with five replications. After 90 days of the sowing, we assessed N and Si contents in shoot system, Si accumulation in shoot system, root, and total, and lignin and protein production. An increase in lignin followed by its reduction was observed from the concentration of 2.0 (4.29) and 4.3 (5.72) mmol L-1 of Si for Viola and Tagetes species, respectively. Silicon application promoted higher lignin content in T. erecta and V. x wittrockiana.